2021
DOI: 10.1186/s12968-021-00805-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional cardiac consequences of rapid hypertension treatment: a cohort study

Abstract: Background Left ventricular (LV) hypertrophy (LVH) in uncontrolled hypertension is an independent predictor of mortality, though its regression with treatment improves outcomes. Retrospective data suggest that early control of hypertension provides a prognostic advantage and this strategy is included in the 2018 European guidelines, which recommend treating grade II/III hypertension to target blood pressure (BP) within 3 months. The earliest LVH regression to date was demonstrated by echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Despite our selection of primarily patients with hypertension (>90%), LVMI (determined with cardiac MRI analysis in the core laboratory) was relatively low and did not progress substantially in the placebo group. This finding is consistent with more recent literature on hypertension 26 , 27 and is likely explained by the intensification of antihypertensive treatments according to recent guidelines. Indeed, approximately half of the patients in each treatment group were taking an angiotensin-converting enzyme inhibitor, and approximately a third were taking an angiotensin receptor blocker; both medication classes have known antihypertrophic effects.…”
Section: Discussionsupporting
confidence: 93%
“…Despite our selection of primarily patients with hypertension (>90%), LVMI (determined with cardiac MRI analysis in the core laboratory) was relatively low and did not progress substantially in the placebo group. This finding is consistent with more recent literature on hypertension 26 , 27 and is likely explained by the intensification of antihypertensive treatments according to recent guidelines. Indeed, approximately half of the patients in each treatment group were taking an angiotensin-converting enzyme inhibitor, and approximately a third were taking an angiotensin receptor blocker; both medication classes have known antihypertrophic effects.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, a cohort study demonstrated a significant reduction in radial strain (RS) after 18 weeks of treatment. Not only this period was shorter than the earliest structural and functional changes detected by echocardiography (24 weeks), but FT-CMR was also able to detect significant RS (short axis) and CS changes, in agreement with reduced LVEDV and LV radial thickness as a consequent of reduced LVH [ 8 ]. Global LS (GLS) along with CMR-obtained lateral mitral annular plane systolic excursion (MAPSE) have been identified as independent predictors of mortality in patients with hypertension [ 9 ].…”
Section: Hypertensionmentioning
confidence: 99%
“…van Cauteren Cardiovascular magnetic resonance accurately detects obstructive coronary artery disease in suspected non-ST elevation myocardial infarction: a sub-analysis of the CARMENTA Trial [ 34 ] David Marlevi False lumen pressure estimation in type B aortic dissection using 4D flow cardiovascular magnetic resonance: comparisons with aortic growth [ 35 ] Theo Pezel Long-term prognostic value of stress perfusion cardiovascular magnetic resonance in patients without known coronary artery disease [ 25 ] Reza Hajhosseiny Clinical comparison of sub-mm high-resolution non-contrast coronary CMR angiography against coronary CT angiography in patients with low-intermediate risk of coronary artery disease: a single center trial [ 36 ] Satoshi Nakamura Long-term prognostic value of whole-heart coronary magnetic resonance angiography [ 37 ] Ying Zhang Comparing cardiovascular magnetic resonance strain software packages by their abilities to discriminate outcomes in patients with heart failure with preserved ejection fraction [ 27 ] Aakash N. Gupta Direct mitral regurgitation quantification in hypertrophic cardiomyopathy using 4D flow CMR jet tracking: evaluation in comparison to conventional CMR [ 38 ] Luuk H.G.A. Hopman Impaired left atrial reservoir and conduit strain in patients with atrial fibrillation and extensive left atrial fibrosis [ 39 ] Andrew N. Jordan Morphological and functional cardiac consequences of rapid hypertension treatment: a cohort study [ 40 ] Shingo Kato Prognostic value of resting coronary sinus flow determined by phase-contrast cine cardiovascular magnetic resonance in patients with known or suspected coronary artery disease [ 41 ] Alastair J. Rankin Myocardial changes on 3T cardiovascular magnetic resonance imaging in response to haemodialysis with fluid removal [ 42 ] Bold manuscripts were also selected for 2021 JCMR Journal Club presentations …”
Section: Continuing Medical Education (Cme) Jcmr J...mentioning
confidence: 99%